Stereotactic radiosurgery for nonfunctioning pituitary tumor: A multicenter study of new pituitary hormone deficiency - Dumot, Chloe; Mantziaris, Georgios; Dayawansa, Sam; Peker, Selcuk; Samanci, Yavuz; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; Abdelkarim, Khaled; El-Shehaby, Amr M N; Emad, Reem M; Abdelsalam, Ahmed Ragab; et al. (Neuro-oncology, 2024)
BACKGROUND: Stereotactic radiosurgery (SRS) is used to treat recurrent or residual nonfunctioning pituitary neuroendocrine tumors (NFPA). The objective of the study was to assess imaging and development of new pituitary hormone deficiency. METHODS: Patients treated with single-session SRS for a NFPA were included in this retrospective, multicenter study. Tumor control and new pituitary dysfunction were evaluated using Cox analysis and Kaplan-Meier curves. RESULTS: A total of 869 patients (male 476 [54.8%], median age at SRS 52.5 years [Interquartile range (IQR): 18.9]) were treated using a median margin dose of 14Gy (IQR: 4) for a median tumor volume of 3.4 cc (IQR: 4.3). With a median radiological follow-up of 3.7 years (IQR: 4.8), volumetric tumor reduction occurred in 451 patients (51.9%), stability in 364 (41.9%) and 54 patients (6.2%) showed tumor progression.The probability of tumor control was 95.5% (95% Confidence Interval [CI]: 93.8-97.3) and 88.8% (95%CI: 85.2-92.5) at 5 and 10 years, respectively. A margin dose >14 Gy was associated with tumor control (Hazard Ratio [HR]:0.33, 95% CI: 0.18-0.60, P < 0.001). The probability of new hypopituitarism was 9.9% (95% CI: 7.3-12.5) and 15.3% (95% CI: 11-19.4) at 5 and 10 years, respectively. A maximum point dose >10 Gy in the pituitary stalk was associated with new pituitary hormone deficiency (HR: 3.47, 95% CI: 1.95-6.19). The cumulative probability of new cortisol, thyroid, gonadotroph, and growth hormone deficiency was 8% (95% CI: 3.9-11.9), 8.3% (95% CI: 3.9-12.5), 3.5% (95% CI: 1.7-5.2), and 4.7% (95% CI: 1.9-7.4), respectively at 10 years. CONCLUSIONS: SRS provides long-term tumor control with a 15.3% risk of hypopituitarism at 10 years.
Keywords: Pituitary Neoplasms; Female; hypofyzární hormony; výsledek terapie; ženské pohlaví; Pituitary Hormones; lidé; Treatment Outcome; následné studie; radiochirurgie; retrospektivní studie; Radiosurgery; Follow-Up Studies; Male; nádory hypofýzy; hypopituitarismus; lidé středního věku; mužské pohlaví; Retrospective Studies; Middle Aged; Hypopituitarism; Humans